PENINGKATAN PENGETAHUAN REMAJA TENTANG PENTINGNYA MINUM TABLET Fe SAAT MENSTRUASI DI SMA BK 06 JUWANGI - S. SUPARMI (P3M Universitas Aisyiyah Surakarta, 2020)
Abstract In young women, menarche and mensis begin to occur accompanied by the disposal of a number of Fe (Djaeni, 2004). Menarche is the first menstruation of women that generally occurs around the age of 10-11 years. The output produced is an increase in adolescent knowledge about anemia and the benefits of Fe. The method of service used in the partner group was counseling to young women at BK 06 Vocational High School class X which amounted to 35 female students, who had previously conducted a pre-test and post-test to determine adolescent knowledge about anemia and the benefits of Fe. Community service conducted at BK 06 Juwangi High School was carried out by involving 35 X grade students. At the beginning of the activity the extension team introduced activities followed by giving a questionnaire to determine the level of knowledge of young female students about anemia and the benefits of Fe. Of the 35 adolescents all have experienced menstruation. The results of the pre-test and post-test analysis were carried out, it was seen that the level of knowledge of the counseling participants before and after the provision of information experienced an increase in knowledge. Before giving counseling to teenagers who knew about the benefits of Fe there were 10 female students, after being given counseling there were 30 female students. Providing information to adolescents in the form of counseling on Mentrasi, Anemia, and the Importance of Fe is very necessary for adolescents who experience anemia, because one of the effects of anemia is affecting student achievement.